2012
DOI: 10.5755/j01.em.17.1.2251
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Corporate Governance System and Quality of Reported Earnings: Evidence From Cee Companies

Abstract: Previous research on Central and Eastern European countries showed that the lower is corporate governance quality the better is the firm's financial performance. One of the explanations for this phenomenon is that weak corporate governance is associated with the low earnings quality, which the present study looks into. The analysis, which was made on 118 companies quoted on Central and Eastern European stock exchanges, shows a prove to the negative relationship between the quality corporate governance and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…The findings of this study is not in line with the findings of Bistrova and Natalja (2012), Yahya (2014) and Meeampol, et. al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study is not in line with the findings of Bistrova and Natalja (2012), Yahya (2014) and Meeampol, et. al.…”
Section: Discussioncontrasting
confidence: 99%
“…By using the results of the self assessment, it is expected to be able to describe the implementation of CG more comprehensively because it includes all elements of CG. Bistrova and Natalja (2012), found that companies that have good governance will minimize the manipulation of financial statements. Research conducted by Meeampol, et.…”
Section: Introductionmentioning
confidence: 99%
“…This is in the line with the findings of Jere, Khurana, and Pereira (2005) in the Latin American case where they concluded that there is a link between transparency and quality of corporate governance in performance expressed through ROA and their credibility for access in credit (credit rating). In the case of Central and Eastern Europe, such evidence is provided by the Bistrova and Lace (2012), who based on a model that included 21 features of corporate governance, concluded that 25% of the companies with the best characteristics of corporate governance significantly exceed performance of 25% of companies at the bottom of the list in terms of attractiveness, investment access and risk management. Similarly, in the case of Croatia, Kokotec, Čalopa and Detelj (2017), in a sample that included a number of companies listed on the Croatian Stock Exchange found a relevance of the best ranking for companies in terms of the corporate governance index for successful business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Manajemen yang ingin menunjukan kinerja yang baik dapat termotivasi untuk memanipulasi laporan keuangan agar bisa mencapai laba seperti yang diinginkan oleh pemilik (Sari & Putri, 2014). Bistrova & Lace (2012) menyatakan bahwa perusahaan akan meminimalisasi adanya manipulasi laporan keuangan apabila mempunyai tata kelola yang baik. GCG dapat meningkatkan kinerja perusahaan melalui pengawasan kinerja manajemen serta menjamin terciptanya akuntabilitas manajemen terhadap pihak investor berdasarkan peraturan yang ada (Kori & Rasmini, 2017).…”
Section: Pendahuluanunclassified